Sediment transport and roughness coefficients generated by flexible vegetation patches in the emergent and submerged conditions in a semiarid alluvial open-channel - Douglas Monteiro Cavalcante (Elsevier, 2021)
In the semiarid environment, low vegetation cover and deforestation on the banks of rivers represent a strong impact on the flow resistance process, altering the interaction of the flow with the banks, one of the conditioning factors of the morphological balance of the river channel. In extreme hydrological events, turbulence and high speeds can cause a marked erosion process at the banks, increasing the sediment yield. This study aimed to monitor water and solid discharges through direct hydrosedimentometric measurements, as well as to estimate, using a simplified model based on force balance, the hydraulic roughness coefficients generated by flexible vegetation element of the Ipomoea pes-caprae species under emergent and submerged conditions. The total annual rainfall for 2019 was 748.5 mm year−1, above the historical mean (642.80 mm year−1). The mean depth (h = 0.24 m) and flow (Ql = 0.15 m3 s−1) rates were highly correlated as a power function (R2 = 0.8041). In general, without specifically considering the effect of vegetation, the flow regime was characterized as turbulent and subcritical flow (Re = 66,634.65 dim. and Fr = 0.16 dim.), respectively. The suspended sediment concentration (CSS), suspended sediment (QSS) and bedload (QBed) discharges presented mean values of 409.41 mg L−1, 6.23 t day−1 and 0.069 t day−1, respectively. The total sediment yield (Yt) was 1.90 t km−2 year−1. The vegetation effect was analyzed on the right (RB) and left (LB) banks, where the stems of I. pes-caprae were concentrated between 0.22 and 0.40 m and 0.66–1.20 m from the banks, respectively. On the RB, the shear (1.0 < Sr < 1.95), free flow (0.27 < Sr < 1.0) and the transition (Sr = 1) zones were identified. On the LB, just emergent condition (Sr < 1.0) was indetified. The following relationship were found between vegetation drag coefficient (C′D), stem Reynolds number (Red), plant density Reynolds number (Rev) and Froude number (Fr) on the RB: C′D (1.22–12.46 m−1); Red (567 < Red < 2224), Rev (1305 < Rev < 35,011) and Fr = 0.14; on the LB: C′D (2.10–1168.29 m−1); Red (57 < Red < 1427), Rev (2615 < Rev < 167,534) and Fr = 0.08. These results demonstrate that the aquatic vegetation directly influences the river dynamics; the density vegetation having a hydraulic impact on the flow transport capacity, that is, as the C′D increases, it increases the resistance of the vegetation to the flow and decreases the capacity of transport of sediments.